228k views
5 votes
What is the result of subtracting the second equation from the first? -3x+2y=7 -3x-2y=4

User Karol F
by
6.0k points

2 Answers

5 votes

Answer:

4y=3

Explanation:

User Flacnut
by
6.0k points
3 votes

The result of subtracting the second equation from the first is
y = (3)/(4)

Solution:

Given system of equations are:

-3x + 2y = 7 ----- eqn 1

and -3x - 2y = 4 ---- eqn 2

We have to find the result of subtracting the second equation from the first

So we have to subtract second equation from the first

-3x - 2y = 4

-3x + 2y = 7

(-) -----------------

-4y = -3

4y = 3


y = (3)/(4)

Thus the result of subtracting the second equation from the first is
y = (3)/(4)

User Rahul Dagli
by
5.3k points